A Case of Successful Surgical Resection of Locally Advanced (T4) Lung Cancer Utilizing a Multi-Disciplinary Approach Involving Previously Unresectable Structures - Meadhbh Ni Mhiochain de Grae; William P. Duggan; Paul Carroll; Alan Soo (International Journal of Medical Students)
Background: